The Balinese Li Ceremony Tradition as Evidence of the Legacy of Animistic Beliefs and Dynamism in the Community of Datar Village, Muaradua District, South Oku Regency (2007-2014) - Heryati; Yusinta Tia Rusdiana; Khairul (Keraton: Journal of History Education and Culture, 2025)
The origin and owner ceremony tradition Li Bali are the property of the tribe Power is taken from the highlands of the mountain areas Seminung / Lake Ranau, then this tradition brought by the power spread of riparian komering in Muaradua to go into the rural areas as well as in the village of Flat , Li Bali ceremony tradition is a tradition or custom series of activities undertaken by the Power to seek peace, and demand protection from spirits who inhabit the forest in time would dilakukanya forest clearing as a farmland. In this study the author uses descriptive qualitative method. This study shows that (1) Incidence ceremony tradition Li Bali due to the inclusion of tribal power in the village Datar who believe in ancestral spirits, (2) procession Li Bali consists of four stages, (3) With the aim of asking for peace, and protection against the spirit of the forest, offerings, spells and public opinion showed evidence of the trust Animism, and black chicken is believed capable of providing peace and can bring sustenance evidence Of the dynamism of confidance.